PORTFOLIO ASSESSMENT IMPACT TO THE STUDENTS’ PARAGRAPH WRITING - Ferlya Elyza; Yusrizal (Jurnal Visipena, 2018)
Begin with the assumption that Portfolio Technique is a good technique in writing skill, the researcher explored a research conducted at University of Abulyatama. It was a quantitative research design. The population of this research was the fourth semester students of University of Abulyatama. There were twelve students, as the sample. Based on the research findings, the writer found that the mean score of pretest was 53, 04 and the mean score of posttest was 87, 5. The result of t-score from pre test and post test was 6,60 and t- table for degree of freedom (df) from the twelve students was 1,711 in the significance of 0,05. It indicated that t-score > t- table. Thus, it also indicated that the hypothesis was accepted. Questionnaires response also reflected that this technique is very helpful in helping students’ writing.